2007
DOI: 10.1038/sj.ejhg.5201897
|View full text |Cite
|
Sign up to set email alerts
|

A functional mutation in the LDLR promoter (−139C>G) in a patient with familial hypercholesterolemia

Abstract: A novel sequence change in repeat 3 of the promoter of the low-density lipoprotein receptor (LDLR) gene, À139C4G, has been identified in a patient with familial hypercholesterolemia (FH). LDLR -139G has been passed to one offspring who also shows an FH phenotype. Transient transfection studies using luciferase gene reporter assays revealed a considerable reduction (7471.4% SEM) in reporter gene expression from the À139G variant sequence compared to the wild-type sequence, strongly suggesting that this change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Promoter mutation-induced diseases have been reported previously (Plenge et al, 1997;Almeida et al, 2006;Guyant-Marechal et al, 2007;Smith et al, 2007). There is still no report regarding the relationship between promoter mutation and epilepsy, although it has been proved that SME is caused by reduced levels of sodium channels and loss of function resulting from SCN1A abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter mutation-induced diseases have been reported previously (Plenge et al, 1997;Almeida et al, 2006;Guyant-Marechal et al, 2007;Smith et al, 2007). There is still no report regarding the relationship between promoter mutation and epilepsy, although it has been proved that SME is caused by reduced levels of sodium channels and loss of function resulting from SCN1A abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The substituted nucleotide is not a strongly conserved base of the SP1 binding site, and this mutation reduced SP1 binding affinity and led to FH (26). In addition, two more mutations in the LDLR gene, -49C>T and -139C>G, have been identified, with one of these shown to induce the loss of SP1 binding in a patient with FH (27,28). The SPI1 gene encodes an ETS-domain transcription factor that activates gene expression during myeloid and B-lymphoid cell development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, long noncoding RNA (lncRNA) facilitates chromatin remodeling, small nuclear RNA (snRNA) mediates splicing, and cytoplasmic microRNA (miRNA) destabilizes RNA and/or microRNA genetics of lipid-related disorders affi nity for one or more TFs, and the resulting effect on transcription could directly infl uence lipid metabolic pathways. For example, several single nucleotide polymorphisms (SNP) in the core promoter region of the low-density lipoprotein receptor ( LDLR ) gene have been shown to abolish binding of the transcription factor Sp1 (49)(50)(51)(52)(53), which leads to familial hypercholesterolemia (FH). As another example, a very recent study demonstrated that the minor allele of the SNP rs12740374, located within an LRE at the 1p13 locus, dramatically increases the binding affi nity for the transcription factor CEBPA, which in turn alters the hepatic expression of the gene sortilin 1 ( SORT1 ), leading to impaired lipoprotein metabolism ( 54,55 ).…”
Section: Hepatic Mirnas and Lipid Homeostasismentioning
confidence: 99%